2020
DOI: 10.1039/c9mh00714h
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in manipulation of micro- and nano-objects with magnetic fields at small scales

Abstract: Magnetic manipulation is very promising for the motion control of micro- and nano-objects, which has wide applications in the mixing, trapping, colloidal assembly and object transport, and the recent progress in these areas is reviewed in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(72 citation statements)
references
References 297 publications
0
71
0
1
Order By: Relevance
“…Comparing with other methods, magnetic interaction exhibits its unique advantages in the use of self‐assembly. For instance, magnetic force has strong penetration which helps it manipulate the objects behind the barriers, such as glass and biological matter, without direct contact [37] …”
Section: Self‐assembly Through Various Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing with other methods, magnetic interaction exhibits its unique advantages in the use of self‐assembly. For instance, magnetic force has strong penetration which helps it manipulate the objects behind the barriers, such as glass and biological matter, without direct contact [37] …”
Section: Self‐assembly Through Various Mechanismsmentioning
confidence: 99%
“…For instance, magnetic force has strong penetration which helps it manipulate the objects behind the barriers, such as glass and biological matter, without direct contact. [37] The number of particles that can be magnetically manipulated to form complex MNRs structures includes ferromagnetic particles, Janus particles with iron oxide, patches of magnetically capped particles and metal deposits, etc. For example, Mojca Vilfan et al used superparamagnetic particles (4:4 mm) to form artificial biomimetic cilia (long chain, L ¼ 31 mm), as displayed in Figure 3a, which could mix and pump of fluids by mimicking the motion of cilia.…”
Section: Magnetic Forcementioning
confidence: 99%
“…1 Later, it was found that nanostructures can be manipulated with the use of an electromagnetic wave. In 2018, the Nobel Prize in physics was awarded for the creation of nanooptical tweezers, 2 and further solutions have followed, including methods of manipulating nano-and micro-objects with the use of a magnetic eld 3 and manipulating objects smaller than 100 nm optically. 4 Technologies for manipulating atomic objects and nanoclusters allow for the creation of many interesting individual nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…[ 17,18 ] In fact, the aggregation of multiple beads occurs because the energy well created by the external field is larger than the nano‐microbeads used for labels and thus multiple beads gather at a single energy well. [ 18,19 ] Here, since the size of the potential energy well created by bulk magnets or magnetic coils is too large to confine a single bead, the interparticle distance of trapped beads cannot be controlled individually. [ 20,21 ]…”
Section: Introductionmentioning
confidence: 99%